Complementary and Alternative Treatments for Cancer Prevention and Cure (Part 1) - Abdul, Kader Mohiuddin (Journal of Experimental and Clinical Toxicology, 2019)
Many lay people along with some so called “key opinion leaders” have a common slogan “There's no answer for cancer”. Again, mistake delays proper treatment and make situation worse, more often. Compliance is crucial to obtain optimal health outcomes, such as cure or improvement in QoL. Patients may delay treatment or fail to seek care because of high out-of- pocket expenditures. Despite phenomenal development, conventional therapy falls short in cancer management. There are two major hurdles in anticancer drug development: dose-limiting toxic side effects that reduce either drug effectiveness or the QoL of patients and complicated drug development processes that are costly and time consuming. Cancer patients are increasingly seeking out alternative medicine and might be reluctant to disclose its use to their oncology treatment physicians. But there is limited available information on patterns of utilization and efficacy of alternative medicine for patients with cancer. As adjuvant therapy, many traditional medicines shown efficacy against brain, head and neck, skin, breast, liver, pancreas, kidney, bladder, prostate, colon and blood cancers. The literature reviews non-pharmacological interventions used against cancer, published trials, systematic reviews and meta-analyses.
Keywords: Cancer care; alternative therapy; complimentary medicine; non-pharmacological cancer treatment